2018
DOI: 10.3389/fimmu.2018.02647
|View full text |Cite
|
Sign up to set email alerts
|

ALS-Associated E478G Mutation in Human OPTN (Optineurin) Promotes Inflammation and Induces Neuronal Cell Death

Abstract: Amyotrophic Lateral Sclerosis (ALS) is a group of neurodegenerative disorders that featured with the death of motor neurons, which leads to loss of voluntary control on muscles. The etiologies vary among different subtypes of ALS, and no effective management or medication could be provided to the patients, with the underlying mechanisms incompletely understood yet. Mutations in human Optn (Optineurin), particularly E478G, have been found in many ALS patients. In this work, we report that NF-κB activity was inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 44 publications
2
59
0
Order By: Relevance
“…Besides, mutations are suggested to activate the inflammatory factors, which also contribute to disease progression. 177 As found in recent studies, OPTN will translocate to damaged mitochondria, which is dependent on Parkin ubiquitination of mitochondria. 175 169,183,184 In addition, VCP also exhibits some properties similar to OPTN;…”
Section: Optn/tbk1mentioning
confidence: 68%
See 1 more Smart Citation
“…Besides, mutations are suggested to activate the inflammatory factors, which also contribute to disease progression. 177 As found in recent studies, OPTN will translocate to damaged mitochondria, which is dependent on Parkin ubiquitination of mitochondria. 175 169,183,184 In addition, VCP also exhibits some properties similar to OPTN;…”
Section: Optn/tbk1mentioning
confidence: 68%
“…Moreover, OPTN mutations have been shown in previous studies to enhance NF‐κB activity and impede intracellular transport. Besides, mutations are suggested to activate the inflammatory factors, which also contribute to disease progression …”
Section: Mitophagy and Neurodegenerative Diseasesmentioning
confidence: 99%
“…One group initially reported that OPTN −/− mice had a slight increase in proinflammatory cytokines, dysmyelination and deficits in vertical rearing activity, but other studies reported no neuroinflammation, dysmyelination and/or neurological defects ( Ito et al , 2016 ; Slowicka et al , 2016 ; Dermentzaki et al , 2019 ). However, an ubiquitin-binding optineurin patient mutation (E478G) lentivirally delivered to the mouse motor cortex, triggered secretion of proinflammatory cytokines and neuronal death ( Liu et al , 2018 ). Therefore, although most studies dismissed excessive inflammation as a mechanism of action of OPTN mutations in ALS, additional functional studies will be necessary to understand if individual OPTN mutations such as E478G act by distinct pathogenic mechanisms.…”
Section: How Does Immunity Turn From Friend To Foe During Als?mentioning
confidence: 99%
“…The E478G mutation in the UBAN of OPTN abolishes its NF-κB suppressive activity 23 , as residues involved in linear ubiquitin-binding correspond to the residues crucial for keeping NF-κB inactive 24 . The mutations result in significant up-regulation of IL-1β, causing neuroinflammation and neuronal cell death of motor neurons, leading to Amyotrophic Lateral Sclerosis 25 .…”
Section: Discussionmentioning
confidence: 99%